Implementasi Model Pembelajaran Example Non Example untuk Meningkatkan Hasil Belajar Ilmu Pengetahuan Sosial Siswa Kelas VI.B SD Negeri 46 Cakranegara - Putra, Adi Wiratman (MASALIQ, 2023)
The purpose of this study was to determine the increase in social science learning outcomes through the implementation of the Example Non Example learning model for Class VI.B students at SD Negeri 46 Cakranegara Odd Semester in the Academic Year 2022/2023. This research consists of two cycles. The data collection instruments in this study were teacher performance observation sheets, student activity, and evaluation questions at the end of each cycle. Based on the results of the research and discussion, it can be concluded that there has been an increase in teacher performance and student activity by applying the examples and non-examples methods for each cycle. In cycle I, teacher performance only reached 75.00% and for cycle II it increased to a good category with a percentage of 90.63%. In observing student learning activities also seen an increase in each cycle. This can be shown in cycle I which reached 72.50% which was in the sufficient category and cycle II increased to 87.50% in the good category. The results of observing teacher performance and student activities have consistently increased, followed by an increase in learning outcomes. The student completeness score on the results of the evaluation of conditions before the action with a percentage of 69.57% and in cycle I was in the good category with a percentage of 82.65%. Then for the results of the evaluation in cycle II, the student completeness score increased to 100% in the very good category. So the results of social studies class VI.B students at SD Negeri 46 Cakranegara can be improved by applying examples and non-examples methods.